Subclonal evolution of a classical Hodgkin lymphoma from a germinal center B‐cell‐derived mantle cell lymphoma. Issue 4 (29th August 2013) - Schneider, Stefanie; Crescenzi, Barbara; Schneider, Markus; Ascani, Stefano; Hartmann, Sylvia; Hansmann, Martin‐Leo; Falini, Brunangelo; Mecucci, Cristina; Tiacci, Enrico; Küppers, Ralf
<x xml:space="preserve">Abstract</x> Composite lymphomas (CL) represent the occurrence of two distinct lymphomas in the same patient. Often, CL share a common cellular origin, thus representing a unique model to investigate the multistep genetic path leading to lymphomagenesis in general and to the specific development of each distinct lymphoma component in particular. Here, we present the molecular analysis of a case consisting of an unusual Hodgkin lymphoma (HL) and a mantle cell lymphoma (MCL), intimately admixed within one another in lymph nodes and bone marrow yet phenotypically distinct, in a patient who first presented with splenic/leukemic MCL two years earlier. MCL and Hodgkin and Reed/Sternberg (HRS) cells harbored identical immunoglobulin (Ig) VH gene rearrangements with shared somatic mutations, proving their common clonal origin from a (post‐)germinal center (GC) B cell. This also demonstrates the (post‐)GC origin of MCL with mutated IgV genes. Both lymphomas carried the same CCND1/IGH translocation and, unexpectedly for HL, expressed cyclin D1 and OCT2. Thus, HRS cells are able to preserve IGH locus activity (otherwise usually silenced in HL) to promote expression of an oncogene translocated into this locus. Both lymphoma populations further showed an identical TP53 function‐impairing mutation, and later acquired a TP53 heterozygous deletion independently from one another (convergent evolution). The surprisingly close genetic relationship of the lymphomas, together with their histological intermingling and the clinical history of the patient, suggests subclonal evolution of HL from MCL as a plausible pathway in alternative to that so far described in CL, i.e. separate development from a common precursor.